Biodegradable sustained-release microneedle patch loaded with clindamycin hydrochloride: a breakthrough in acne management - Fan, Haomei; Liao, Ruohan; Yang, Yiling; Xing, Yan; Zhang, Chengdong; Luo, Xuwei; Pu, Chao; Wu, Liling; Li, Xingping; Zhao, Juhua; Xiao, Dongqin (Frontiers in Pharmacology, 2025)
BackgroundClindamycin hydrochloride, a first-line antibiotic for acne treatment, faces challenges with poor skin penetration due to its hydrophilicity and the barrier posed by the stratum corneum. To address this limitation, we developed gelatin-methacryloyl (GelMA) hydrogel-based biodegradable microneedles (GM-Clin-MN) for sustained intradermal drug delivery, thereby enhancing therapeutic efficacy.MethodsThe microneedle patches loaded with 1 wt% clindamycin hydrochloride were fabricated using PDMS molds and characterized through scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and fluorescence microscopy. Drug loading and release were assessed using UV-Vis spectroscopy at 520 nm, while mechanical strength was evaluated with a universal testing machine. Skin penetration was tested on ex vivo rat abdominal skin. Biosafety was determined through human skin fibroblast (HSF) cytotoxicity and hen’s egg test-chorioallantoic membrane (HET-CAM) irritation tests. Antibacterial efficacy against Cutibacterium acnes (C. acnes) was measured via colony counting. In vivo acne treatment of the microneedles was evaluated in a rat acne model. Gross morphological changes, histological sections, and immunohistochemical staining were used to evaluate the efficacy and potential mechanisms of acne treatment.ResultsClindamycin hydrochloride-loaded GelMA microneedles (GM-Clin-MN) achieved a drug loading of 0.49 ± 0.025 μg/needle, exhibiting rapid release on Day 1 (54.8% ± 2.1%) and sustained release by Day 10 (72.1% ± 1.5%). The microneedles penetrated the skin to a depth of 658 ± 66 μm, swelled by 185.4% ± 12.1%, and completely dissolved within 10 min. GM-Clin-MN displayed no cytotoxicity or skin irritation and effectively inhibited the growth of C. acnes (bacterial inhibition rate of 100%). In vivo studies revealed that acne-related inflammation was effectively suppressed with potential anti-scarring properties, characterized by reduced pro-inflammatory IL-1β levels, increased anti-inflammatory IL-10 expression, and diminished MMP-2 activity — a key enzyme in collagen overproduction during scarring.ConclusionGM-Clin-MN enables sustained, minimally invasive clindamycin delivery through the stratum corneum, offering a dual-action therapeutic strategy that combines potent antibacterial activity with anti-inflammatory modulation for acne management.